Utilization of Brown Rice as Fortification of Putu Mayang - Nur FitriAnisah Nasution; Vany Octaviany (Publikasi Indonesia, 2025)
In this day and age, it is very difficult to find food that is rich in nutrients and nutritious, one of the foods that is rich in nutrients can be a typical Betawi food, namely putu mayang cake. If innovated with brown rice, putu mayang cake will be more nutritious and have a lot of nutrients. As well as the nutrition and nutritional content of brown rice, putu mayang cake will look more nutritious and rich in nutrients. Experimental research on the manufacture of putu mayang involves the division of research subjects or objects into control groups and treatment groups, where the treatment group is subjected to certain treatments while the control group is not. This research aims to uncover the Utilization of Brown Rice as a Fortification of Putu Mayang. This study uses an experimental design with a variation of the addition of brown rice as an addition to fortification in the manufacture of putu mayang. This variation was carried out to determine the effect of the addition of brown rice on the fortification of putu mayang cake making. The data from the organoleptic test results include aspects of taste, color, and texture aroma with the use of brown rice flour. The power test of the level of favorability or hedonic test was carried out on the panelists, which amounted to 30 people. Based on the results of consumer acceptance, consumers accept a variety of wheat flour mixtures with different levels, this is due to the large nutritional content possessed by brown rice flour, but the taste of Putu Mayang is not so disturbed, it's just that the texture is a little hard because the more brown rice flour content is included, the less coarse the texture will be.